CONTRIBUTION À L’ÉTUDE DE LA BIOACCUMULATION MÉTALLIQUE DANS LES SÉDIMENTS ET LES ORGANISMES AQUATIQUES DU LITTORAL DE SAIDIA (MAROC ORIENTAL) - Aouatif Fahssi; Abdelhafid Chafi (European Scientific Journal, ESJ, 2015)
The result of the coastal metal contamination in the extreme East of Morocco was based on sampling and the search for metal contamination by lead, zinc, cadmium, and iron respectively. This search was done in marine water, sediments, and in the sea. Urchin Paracentrotus lividus; benthic echinoderm is common in the eastern Mediterranean coast of Morocco with two sampling series (July 2011 and March 2012). The objective of this study is to evaluate the distribution of some heavy metals in the Saidia coastline, through the Biological indicator, Paracentrotus lividus. The heavy metal content (iron, zinc, lead and cadmium) in water, sediment, and marine organisms, were studied in four stations at the coast Saidia. The study revealed the presence of very high concentrations of metals, especially with regard to iron and zinc. Lead has relatively high values, while the cadmium is virtually absent in all samples. However, the results support a finding which is similar to the bio-accumulated metals by the sea urchin elements and those detected in water and sediment. The existence of a significant correlation between iron, zinc, and lead shows that there is a high chemical affinity between these three metals. Overall, this study allows us to identify the presence of heavy metals in water, sediment, and aquatic organisms of coastal Saidia, which is seriously disrupted by various domestic discharges, port, industrial and agricultural wastes.